2021
DOI: 10.1371/journal.pcbi.1008777
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the contribution of tumor mutational phenotypes to cancer progression risk

Abstract: Cancer occurs via an accumulation of somatic genomic alterations in a process of clonal evolution. There has been intensive study of potential causal mutations driving cancer development and progression. However, much recent evidence suggests that tumor evolution is normally driven by a variety of mechanisms of somatic hypermutability, which act in different combinations or degrees in different cancers. These variations in mutability phenotypes are predictive of progression outcomes independent of the specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Consequently, quantifying the strength of selection operating on them is not presently feasible. Thus far, research has indicated that copy-number changes and structural variants do not substantially influence selection on simple nucleotide variations, and have instead orthogonal effects in cancers [38].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, quantifying the strength of selection operating on them is not presently feasible. Thus far, research has indicated that copy-number changes and structural variants do not substantially influence selection on simple nucleotide variations, and have instead orthogonal effects in cancers [38].…”
Section: Discussionmentioning
confidence: 99%